Sepuluh Modal Agar Menjadi Guru Profesional - Yazidul Busthomi; Syamsul A’dlom (Salimiya: Jurnal Studi Ilmu Keagamaan Islam, 2021)
Abstract Professional teachers are people who have special abilities and expertise in the field of teacher training so that they are able to carry out their duties and functions as a teacher to the maximum capacity. Or in other words, professional teachers are people who are well educated and trained and have rich experience in their fields. The ten assets to become a professional teacher are as follows: 1) Collective teacher activities that improve teacher competence and/or professionalism, 2) Education and training, 3) Apprenticeship, 4) Scientific publication of research results or innovative ideas, 5) Innovative work, 6) Presentation at scientific forums, 7) Publication of textbooks that pass the assessment by the national education standards body, 8) Publication of enrichment books and publication of teacher manuals, 9) Publication of field experiences in special education, 10) Award for achievement or dedication as teachers provided by the government / local government.